2016
DOI: 10.1051/epjconf/201611927004
|View full text |Cite
|
Sign up to set email alerts
|

The Measurement of Tropospheric Temperature Profiles using Rayleigh-Brillouin Scattering: Results from Laboratory and Atmospheric Studies

Abstract: In this letter, we suggest a new method for measuring tropospheric temperature profiles using Rayleigh-Brillouin (RB) scattering. We report on laboratory RB scattering measurements in air, demonstrating that temperature can be retrieved from RB spectra with an absolute accuracy of better than 2 K. In addition, we show temperature profiles from 2 km to 15.3 km derived from RB spectra, measured with a high spectral resolution lidar during daytime. A comparison with radiosonde temperature measurements shows reaso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 11 publications
(12 reference statements)
0
5
0
Order By: Relevance
“…The pressure values adopted in the air experiment are close to 1.0 bar, with the temperatures ranging from 256 K to 340 K, which correspond to real atmospheric situations. The retrieval errors from the method presented in reference [15], [16] are all listed in Table 7 to interpret the optimal model we proposed for the simultaneous retrieval of gas temperature and pressure.…”
Section: Results and Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…The pressure values adopted in the air experiment are close to 1.0 bar, with the temperatures ranging from 256 K to 340 K, which correspond to real atmospheric situations. The retrieval errors from the method presented in reference [15], [16] are all listed in Table 7 to interpret the optimal model we proposed for the simultaneous retrieval of gas temperature and pressure.…”
Section: Results and Analysismentioning
confidence: 99%
“…In other words, for the dual-parameter model, the upper limit of retrieval error in a characteristic model is based on Rayleigh linewidth, and the overall spectral linewidth is minimal when the error of the characteristics is 1 MHz. The accuracy of the retrieval result is acceptable for real remote-sensing applications [16]- [19].…”
Section: B Theoretical Analysis Of Retrieval Model For Temperature Amentioning
confidence: 93%
See 1 more Smart Citation
“…As the echo signal intensity is disturbed by Mie scattering caused by aerosols in the troposphere, the Lidar technique is applied, based on frequency field detection methods such as rotational Raman Lidar [ 1 , 2 ] and Rayleigh Brillouin (RB) Lidar. These techniques function by resolving the spontaneous Rayleigh Brillouin (SRB) spectrum [ 3 , 4 ] to reduce the Mie scattering. The rotational Raman differential backscattering cross-section is smaller than that of Rayleigh scattering, which means that the rotational Raman Lidar need a more powerful laser, a more sensitive receiver system, and more integration time.…”
Section: Introductionmentioning
confidence: 99%
“…Also in 2014, the experimental data demonstrated that temperatures can be retrieved from SRB line shapes at an accuracy of 2 K based on Tenti S6 [ 18 ]. Furthermore, Witschas showed temperature profiles from 2 to 15.3 km derived from the SRB spectrum in 2015 [ 4 ]. The temperature measurements performed at noon showed good agreement to the radiosonde measurements.…”
Section: Introductionmentioning
confidence: 99%